已知 x/(y+z)+y/(z+x)+z/(x+y)=1求 (x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:59:01
已知x/(y+z)+y/(z+x)+z/(x+y)=1求(x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?已知x/(y+z)+y/(z+x)+z/(x+y)=1求(x*x)/(
已知 x/(y+z)+y/(z+x)+z/(x+y)=1求 (x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?
已知 x/(y+z)+y/(z+x)+z/(x+y)=1
求 (x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?
已知 x/(y+z)+y/(z+x)+z/(x+y)=1求 (x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?
因为x/y+z + y/z+x +z/x+y=1
所以x/y+z=1-y/z+x-z/x+y,两边同乘以x
得x^2/y+z=x-xy/z+x-xz/x+y
同理y^2/x+z=y-xy/z+y-yz/x+y,z^2=z-xz/y+z-yz/x+z
所以原式=x+y+z-(xy+zy)/x+z-(xz+yz)/x+y-(yx+zx)/y+z
=x+y+z-y-z-x
=0
已知 x/(y+z)+y/(z+x)+z/(x+y)=1求 (x*x)/(y+z)+(y*y)/(x+z)+(z*z)/(x+y)=?
已知 (x+y-z)/z=(x-y+z)/y=(y+z-x)/x,且xyz≠0,求代数式 ((x+y)(y+z)(x+z))/xyz
分式加减法:已知x+y/z=x+z/y=y+z/x(x+y+z≠0),求x+y-z/x+y+z
已知(x+y)(x+z)=x,(y+z)(y+x)=2y,(z+x)(z+y)=3z,求x,y,z
已知:x^2/(z+y)+y^2/(x+z)+z^2/(x+y)=0,求x/(z+y)+y/(x+z)+z/(x+y)的值.
已知x+y/z=x+z/y=y+z/x(x+y+z≠0),求x+y-z/x+y+z的步骤
已知x+y/z=x+z/y=y+z/x(x+y+z≠0),求x+y-z/x+y+z的步骤
x-y/(z-x)(z-y) 一y-z/(x-y)(x-z) +z-x/(y-z)(y-x)
x^-(y-z)^/(x+y)^-z^
计算(x+y-z)(x-y-z)
计算:(x-y+z)(-x+y+z)
(x+y-z)(x-y+z)=
已知x+y+z=0求证x*x*x+y*y*y+z*z*z=3xyz
已知(y+z)/x=(z+x)/y=(x+y)/z,则(y+z)/x的值是多少
x y y ...y z x y ...y z z x ...y ........z z z ...x 求解行列式.
已知x/(y+z+u)=y/(z+u+x)=z/(u+x+y)=u/(x+y+z)求(x+y)/(z+u)+(y+z)/(x+u)+(z+u)/(x+y)+(u+x)/(y+z)
已知X+Y+Z=0,求(X+Y)(Y+Z)(X+Z)+XYZ的值.
已知x+y+z=0,求(x+y)(y+z)(z+x)+xyz的值